PENGARUH PROFITABILITAS, LIKUIDITAS, KEBIJAKAN DIVIDEN,STRUKTUR MODAL, DAN CORPORATE SOCIAL RESPONBILITYTERHADAP NILAI PERUSAHAAN(Studi Empiris Perusahaan Manufaktur di BEI Tahun 2013-2015) - RACHMA LITASARI, MIFTAH, Eny Kusumawati SE, MM, Ak (2017)
The purpose of this study was to determine the effect of profitability, liquidity, dividend police, capital structure, and corporate social responbility to the value of the company at a manufacturing company in Indonesia Stock Exchange 2013-2015. This study population is listed manufacturing industry in Indonesia Stock Exchange in 2013-2015. Sampling method with purposive sampling method, with some predetermined criteria, the number of samples is 101 manufacturing companies. The research data is secondary data obtained from www.idx.co.id. Data analysis techniques used in this study is multiple linear regression analysis. The results showed that profitability, dividend police, and capital structure has positive significanly to firm value, liquidity and corporate social responbility did not have effect significanly to firm value. The fifth contribution of the independent variables on the dependent variable is the value of the company can be seen from the value Adj. R Square obtained is equal to 0,944. This means that 94,4 percent of the variation of the companies affected by the variable profitability, liquidity, dividend police, capital structure, and corporate social responbility.